2011
DOI: 10.1242/jcs.087510
|View full text |Cite
|
Sign up to set email alerts
|

Changes in BiP availability reveal hypersensitivity to acute endoplasmic reticulum stress in cells expressing mutant huntingtin

Abstract: Huntington's disease (HD) is caused by expanded glutamine repeats within the huntingtin (Htt) protein. Mutant Htt (mHtt) in the cytoplasm has been linked to induction of the luminal endoplasmic reticulum (ER) stress pathway, the unfolded protein response (UPR). How mHtt impacts the susceptibility of the ER lumen to stress remains poorly understood. To investigate molecular differences in the ER in cells expressing mHtt, we used live-cell imaging of a sensitive reporter of the misfolded secretory protein burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 68 publications
(88 reference statements)
1
28
0
Order By: Relevance
“…Alterations in the function of the stress sensors (e.g., Bip, CHOP and ASK1) are implicated in the pathogenesis of HD [14,35]. Here, it was observed that the transcript and protein levels of Bip and CHOP in mHtt expressing cells were signficantly higher than in control Htt expressing N2A cells (Fig.…”
Section: Rosiglitazone Normalizes Er Stress and Improves Survival In mentioning
confidence: 67%
See 1 more Smart Citation
“…Alterations in the function of the stress sensors (e.g., Bip, CHOP and ASK1) are implicated in the pathogenesis of HD [14,35]. Here, it was observed that the transcript and protein levels of Bip and CHOP in mHtt expressing cells were signficantly higher than in control Htt expressing N2A cells (Fig.…”
Section: Rosiglitazone Normalizes Er Stress and Improves Survival In mentioning
confidence: 67%
“…mHtt induces ER stress at an early stage of HD, and pathogenic ER stress from an aging or stressful environment is severe in the late stages of HD [13,14]. Abnormal expression of ER stress genes (e.g., Herpud1, Rrs1, and 3D3/lyric) occurs in HD [35,69]. Following ER stress, CHOP is translocated to the nucleus and can induce cell death proteins and decrease the expression of Bcl-2 [71].…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of Bip1-GFP in C. elegans [64] has been successfully used to quantitatively monitor UPR activation in these organisms. In mammalian cells, our group generated a fluorescent UPR reporter by fusing a portion of the BiP promoter containing ER stress response elements (-169 ERSE) [65] to the red FP tdTomato [66]. This reporter exhibits significant upregulation following treatment of cells with ER stressors such as tunicamycin (Tm) or DTT or upon expression of mutant proteins known to induce the UPR, such as exon1 of the Huntington's disease-associated mutant polyQ protein, huntingtin [66].…”
Section: Approaches For Imaging Er Stress and Upr Activity In Livinmentioning
confidence: 99%
“…FRAP relies on the ability of fluorescently tagged BiP (such as BiP-GFP) to freely diffuse and sample the entire volume of the ER lumen. When a BiP-GFP molecule encounters and binds a misfolded protein, diffusional mobility of BiP-GFP decreases [66, 81]. Changes in BiP-GFP mobility can be quantitated by calculating the protein diffusion coefficient ( D ) using inhomogeneous simulations [82].…”
Section: Approaches For Imaging Er Stress and Upr Activity In Livinmentioning
confidence: 99%
See 1 more Smart Citation